From minimally to maximally invasive; VT ablation in the setting of mechanical aortic and mitral valves. (21st July 2022) - Hawson, Joshua; Kalman, Jonathan; Goldblatt, John; Anderson, Robert D.; Watts, Troy; Hardcastle, Nick; Siva, Shankar; Kumar, Saurabh; Lee, Geoffrey
Abstract: Double mitral and aortic mechanical valves present an access challenge when planning a ventricular tachycardia (VT) ablation. In this case report, we describe a patient who was considered for stereotactic ablative radiotherapy but was unable to proceed due to unfavorable anatomy making them at high risk of fistula formation. The patient went on to have an endocardial VT ablation via mini‐thoracotomy and transapical access without complication. This case highlights the need for careful consideration when planning treatment for patients with double mechanical valves.